Palliative Mustard operation for transposition of the great arteries: late results after 15-20 years. - Sagin-Saylam, G. (1996)
OBJECTIVE--To assess the clinical, functional state, and complications late (15-20 years) after palliative Mustard operation. DESIGN--Examination and evaluation of all patients presenting in adolescence and adult life after palliative Mustard operation for transposition of the great arteries and pulmonary vascular disease. SETTING--Grown-up Congenital Heart Unit specialised in the care of adolescents and adults with congenital heart disease, designated as having "quaternary" status within a tertiary referral centre for cardiac diseases. PATIENTS AND METHODS--Database searched for patients referred after palliative Mustard for classic transposition of the great arteries. Ten patients aged 18-31 (mean (SD) 25.9 (5.2)) years with a palliative Mustard operation performed at age 1.7-15 (mean (SD) 9 (4.6)) years were fully evaluated by echocardiography, exercise testing, Holter monitoring, and magnetic resonance imaging or radionuclide ventriculography, or both 15-20 years later. RESULTS--One patient died aged 25 years with biventricular failure (ability index 3/4), haemoptysis, and atrial flutter, eight were well (ability index 2), and one disabled (ability index 3). Arterial oxygen saturation at rest was 85-98% (mean (SD) 93.8 (4)%) decreasing to 59-87% (mean 77 (9.5)%) after limited exercise. Symptomatic arrhythmias occurred in four patients, atrial flutter being the most common, and two had sinus node dysfunction. Significant tricuspid regurgitation occurred in four patients. CONCLUSION--Patients with palliative Mustard operation have a low incidence of symptomatic ventricular dysfunction and despite exercise limitation by hypoxia, continue to live active, near normal lives until their thirties.